2022
DOI: 10.1002/alz.12567
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin mutations in clinical and neuropathological Alzheimer's disease

Abstract: Introduction: Progranulin (GRN) mutations occur in frontotemporal lobar degeneration (FTLD) and in Alzheimer's disease (AD), often with TDP-43 pathology. Methods:We determined the frequency of rs5848 and rare, pathogenic GRN mutations in two autopsy and one family cohort. We compared Braak stage, β-amyloid load, hyperphosphorylated tau (PHFtau) tangle density and TDP-43 pathology in GRN carriers and non-carriers.Results: Pathogenic GRN mutations were more frequent in all cohorts compared to the Genome Aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…CD55 , expressed in both neurons and glial cells 61 , played a role in Alzheimer’s disease progression by influencing both the complement 62 and inflammatory systems 63 . GRN encoded the protein progranulin, a microglial protein linked to Alzheimer’s disease, acting as a mediator of neuroinflammation and exacerbating tau-related brain pathology 64 . BCAM and SIRPA both encoded glycoproteins of the immunoglobulin superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…CD55 , expressed in both neurons and glial cells 61 , played a role in Alzheimer’s disease progression by influencing both the complement 62 and inflammatory systems 63 . GRN encoded the protein progranulin, a microglial protein linked to Alzheimer’s disease, acting as a mediator of neuroinflammation and exacerbating tau-related brain pathology 64 . BCAM and SIRPA both encoded glycoproteins of the immunoglobulin superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…LGALS9_SLC1A5, and F10_TNFRSF10A communicated frequently in low-CR B cells. The increased chemokine CCL4 and GRN mutations were found to closely associated with AD pathology (36,37), suggesting a poor prognosis in AD patients. Additionally, the pseudotime analysis demonstrated that the CRD is involved in the transformation of naive B cells into GC B cells, thus resulting in the progression of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Variants in the 3'UTR region can impact translation or protein stability, and transcription binding can be impacted by variants in the 5'UTR region. Additionally, GRN-rs5848 is associated with circulating progranulin levels and decreased GRN expression has been implicated in several neurodegenerative diseases, including AD and frontotemporal dementia [52][53][54] . In contrast to previous studies in European populations, the SORL1 locus was not resolved to a single putative causal SNP.…”
Section: Discussionmentioning
confidence: 99%